Nilai-Nilai Puisi “Madura Akulah Darahmu” dalam Kajian Konseling Indigenous Masyarakat Pendalungan - Khairul Bariyyah; Alief Laili Budiyono; Yuana Kristiyorini; Nining Maizura (Universitas Sebelas Maret, 2025)
Indigenous counseling offers an approach that counselors can utilize to address issues within the Pendalungan community. This counseling emphasizes the counselor's direct involvement in assisting clients by leveraging the clients' culture, values, or beliefs to achieve counseling goals. Counselors are also required to pay attention to the unique characteristics of the Pendalungan community.The local wisdom values employed are derived from the poem